“O gênero sempre é novo e velho ao mesmo tempo”. Novidades - Brait, Beth; Pistori, Maria Helena Cruz; Lopes-Dugnani, Bruna; Stella, Paulo Rogério; Gontijo Rosa, Carlos (Bakhtiniana. Revista de Estudos do Discurso, 2023)
Editorial 18.3